Role of sestrin2 in H2O2-induced PC12 apoptosis. (12th April 2017) - Liu, Aiqun; Yu, Qingyun; Xiao, Songhua; Peng, Zhongxing; Huang, Yeqing; Diao, Shengpeng; Cheng, Jing; Hong, Mingfan
Highlights: Sestrin2 has a beneficial effect on PC12 cell apoptosis induced by H2 O2 . H2 O2 induces expression of Sestrin2 in PC12 cells in a time-dependent and dose-dependent manner. Knockdown of Sestrin2 using small RNA interference promotes cell apoptosis induced by H2 O2 . Abstract: Sestrin2 is involved in different kind of cellular response to stress conditions. However, the function of Sestrin2 in oxidative stress related neurological diseases remains unknown. In this study, we tested whether Sestrin2 has a beneficial effect on PC12 cell apoptosis induced by H2 O2 . We found that H2 O2 induces expression of Sestrin2 in PC12 cells in a time-dependent and dose-dependent manner. We also found that Knockdown of Sestrin2 using small RNA interference promotes cell apoptosis induced by H2 O2 . In addition, our results show that the c-Jun NH(2)-terminal kinase (JNK)/c-Jun pathway is activated by H2 O2 . Inhibiting the activity of the JNK pathway and JNK siRNA transfection abolishes the increase of Sestrin2 induced by H2 O2 . These findings suggest that the inductive effect of Sestrin2 is mediated by the JNK/c-Jun pathway. In this study, we investigated the role of Sestrin2 in oxidative stress-induced cell apoptosis using PC12 cells as the model, implying that stimulating expression of Sestrin2 might be considered as a neuroprotective target against H2 O2 -induced oxidative stress.